Cost Calculation in Research and Development of New Validation Methods - Záhorská, Alexandra; Munzarová, Simona; Košťálová, Jana (Univerzita Hradec Králové, 2021)
In this paper, we focus our attention primarily on management tools and techniques that could be applied in the pre-production stage of the production process, respectively in the R&D stage. Attention is focused on Strategic cost management and its tools in R&D. Innovations and R&D are necessary for business to build competitive advantage, but looking closer at R&D activities, we could see constantly increasing costs, the costs of professional staff, instrumentation, aids, etc. So, it is appropriate to find and apply proper management methods, tools and techniques of strategic cost management. This article is based on the results of research dealing with the cost analysis of a newly developed method for the toxicity testing of nanomaterials. For the purposes of analysis and cost calculation, one of the newly developed validation methods for determining the toxicity of nanomaterials was selected. In the conditions of laboratory research, it was found that mainly activities are the main cost object for cost calculations. It seems advantageous to use the Activity Based Costing method for managing or determining the costs at R&D laboratories or for cost calculations of the newly developed methods.
Kalkulace nákladů ve výzkumu a vývoji nových metod ověřování
Keywords: costing; R&D activities; testing; nanomaterials; activity-based costing; kalkulace nákladů; činnosti R&D; nanomateriály; kalkulace nákladů dle činností